Multifunctional Integrated Organic–Inorganic-Metal Hybrid Aerogel for Excellent Thermal Insulation and Electromagnetic Shielding Performance - Niu, Zhaoqi; Qu, Fengjin; Chen, Fang; Ma, Xiaoyan; Chen, Beixi; Wang, Luyao; Xu, Miao; Wang, Shumeng; Jin, Liang; Zhang, Chengshuang; Hou, Xiao (Nano-Micro Letters, 2024)
Vehicles operating in space need to withstand extreme thermal and electromagnetic environments in light of the burgeoning of space science and technology. It is imperatively desired to high insulation materials with lightweight and extensive mechanical properties. Herein, a boron–silica–tantalum ternary hybrid phenolic aerogel (BSiTa-PA) with exceptional thermal stability, extensive mechanical strength, low thermal conductivity (49.6 mW m−1 K−1), and heightened ablative resistance is prepared by an expeditious method. After extremely thermal erosion, the obtained carbon aerogel demonstrates noteworthy electromagnetic interference (EMI) shielding performance with an efficiency of 31.6 dB, accompanied by notable loading property with specific modulus of 272.8 kN·m kg−1. This novel design concept has laid the foundation for the development of insulation materials in more complex extreme environments. Highlights: 1 The homogeneous hybridization of organic–inorganic-metal elements in 3D aerogel was achieved by an expeditious method. 2 The aerogel tightly integrates excellent thermal insulation (49.6 mW m−1 K−1), ablative resistance, mechanical strength, and superhydrophobic properties. 3 The ablated carbon aerogel combines notable electromagnetic interference shielding properties (31.6 dB) and load-carrying properties (272.8 kN·m kg−1).